PENGARUH BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN DI THE AXANA HOTEL PADANG - Susiani, Susiani; Suyuthie, Hijriyantomi (Mimbar : Jurnal Penelitian Sosial Dan Politik, 2019)
PThis research was conducted from the observations of the author during the Industry Field Experience (PLI) 2 and pre-research on employee performance at The Axana Hotel Padang. The purpose of this study was to analyze the influence of organizational culture on employee performance at The Axana Hotel Padang. This type of research is classified in quantitative research with a causal associative approach, the study population of 80 employees at The Axana Hotel Padang and used as a sample. The way to determine the sample is saturated sample. Collection of organizational culture data based on indicators according to Edison, et al in Hendra (2018: 74), namely self-awareness, aggressiveness, personality, performance, team orientation. obtained from distributing questionnaires using the Likert scale method that has been tested for validity and reliability, employee performance data with work performance indicators and work attitudes were obtained from HRD The Axana Hotel Padang. Data analysis through simple linear regression with the help of SPSS version 16.00. The results showed that: Organizational Culture classified in the good category has a percentage of 58.75%, Employee Performance is classified in the good category has a percentage of 70%, and the influence of organizational culture variables on employee performance by 6.2% while 93.8% is determined by factors other